2018
DOI: 10.1007/s11356-018-2450-z
|View full text |Cite
|
Sign up to set email alerts
|

Nontuberculous mycobacteria in the environment of Hranice Abyss, the world’s deepest flooded cave (Hranice karst, Czech Republic)

Abstract: Nontuberculous mycobacteria (NTM) are widely distributed in the environment. On one hand, they are opportunistic pathogens for humans and animals, and on the other hand, they are effective in biodegradation of some persistent pollutants. Following the recently recorded large abundance of NTM in extreme geothermal environments, the aim of the study was to ascertain the occurrence of NTM in the extreme environment of the water zone of the Hranice Abyss (HA). The HA mineral water is acidic, with large concentrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 63 publications
1
6
0
Order By: Relevance
“…The microbial survey carried out in the Santa Margherita's cave was aimed to evaluate the microbial community harboured by this unique environment on one hand, and on the other hand, to give insights about the possible role of microorganisms as a potential risk for paintings conservation. Similarly to what was previously unveiled in related cave environments (Ma et al 2015;Portillo et al 2008;Pavlik et al 2018;Yasir 2018;Alonso et al 2019), the bacterial community of both east and west walls was represented by Firmicutes, Proteobacteria, Bacteroidetes, Actinobacteria, Cyanobacteria, and Gammatimonodota phyla (Fig. 8a).…”
Section: Microbial Characterizationsupporting
confidence: 74%
“…The microbial survey carried out in the Santa Margherita's cave was aimed to evaluate the microbial community harboured by this unique environment on one hand, and on the other hand, to give insights about the possible role of microorganisms as a potential risk for paintings conservation. Similarly to what was previously unveiled in related cave environments (Ma et al 2015;Portillo et al 2008;Pavlik et al 2018;Yasir 2018;Alonso et al 2019), the bacterial community of both east and west walls was represented by Firmicutes, Proteobacteria, Bacteroidetes, Actinobacteria, Cyanobacteria, and Gammatimonodota phyla (Fig. 8a).…”
Section: Microbial Characterizationsupporting
confidence: 74%
“…Another recent study by Pavlik et al (2018) investigated the occurrence of NTM in the extreme environment of the water zone of the Hranice Abyss, Czech Republic, the deepest flooded pit cave in the world [ 232 ]. This cave is characterized by its acidic water, high concentration of CO 2 , and the biofilm communities of slime bacteria.…”
Section: Mycobacteria Ecological Nichesmentioning
confidence: 99%
“…Furthermore, M. elephantis was isolated from low impact rock surfaces [ 233 ], M. gordonae was identified in calcareous siltstone beds [ 234 ], and the Mycobacterium genus was also detected in Khuangcherapuk cave in India [ 235 ]. The overall presence of NTM species in cave oligotrophic environments has been associated with earthworm castings, bat guano, alluvial sediment, and plant material that provide NTM with the necessary organic matter [ 232 ].…”
Section: Mycobacteria Ecological Nichesmentioning
confidence: 99%
“… M. = Mycobacterium ; Risk Group 1 of Agents (low individual and community risk) = includes those microorganisms, bacteria, fungi, viruses, and parasites, which are unlikely to cause disease in healthy workers or animals); Risk Group 2 of Agents (moderate individual risk, limited community risk) = includes pathogens that can cause human or animal disease but under normal circumstances, is unlikely to be a serious hazard to healthy laboratory workers, the community, livestock, or the environment according to the European Union Directive 2000/54/EC (Risk Groups are taken from LPSN https://lpsn.dsmz.de/ ) [ 68 ]; CFU = colony forming unit; V1–7 = villages 1–7 (V1 = Žďár , water stream: Žďárský potok ; V2 = Vysočany , water stream: Bělička ; V3 = Niva , water stream: Bílá voda ; V4 = Ostrov u Macochy , water stream: Lopač ; V5 = Kotvrdovice , water stream: Kotvrdovický potok ; V6 = Podomí , water stream: Podomský potok ; V7 = Březina , water stream: Ochozský potok ), A, B, and C = sampling sites: A = upstream (300–1500 m) the village, B = inside the village (100–300 m) up to wastewater treatment plants (WWTPs), and C = downstream the outflow of WWTPs (10–30 m downstream of the WWTP’s outflow); W water samples were positive only; NK = not known; *found in Bull Rock Cave ( Býčí skála ) located in Moravian Karst ( Moravský kras ) in previous study by Modra et al [ 47 ]: WS = water sediments and/or alluvial material, F = bats and/or earthworms in the cave, B = inside the village up to WWTPs in Rudice and Jedovnice , C = downstream the outflow of WWTPs in Rudice and Jedovnice , **found in Amaterská Cave System located in Moravian Karst in previous study by Modra et al [ 70 ]: CS = cave sediment contaminated by dripping water; numbers of isolates in gray color are showing the species or subspecies isolation from different sampling sites in the same village by Pavlik et al [ 48 ]; ***identified NTM isolates into the species, subspecies, and complexes. …”
Section: Resultsmentioning
confidence: 99%